IgE-Selective Immunoadsorption for Severe Atopic Dermatitis - Kasperkiewicz, Michael; Mook, Sophie-Charlotte; Knuth-Rehr, Diana; Vorobyev, Artem; Ludwig, Ralf J.; Zillikens, Detlef; Muck, Philip; Schmidt, Enno (Frontiers in Medicine, 2018)
Introduction Recent reports proposed the application of immunoadsorption (IA) for patients with recalcitrant atopic dermatitis (AD) and high-serum IgE levels. However, experience with this novel treatment approach, especially with the newly available IgE-specific adsorber, is limited and recommendation for its use in clinical practice awaits evidence from more studies. Materials and methods Patients with severe AD (SCORAD ≥ 60) and total serum IgE levels ≥750 kU/L were included in this study. The treatment protocol consisted of two cycles of five consecutive treatments with IgE-selective IA 3 weeks apart. Results Ten patients were enrolled and four patients completed the study. The mean SCORAD was significantly improved by up to 43% within a few weeks and until the end of a 6-month follow-up period, with 50% of patients achieving an at least 50% individual reduction of the baseline SCORAD. Each IA cycle induced a temporal average decrement of total serum levels of IgE, IgM, IgA, and IgG by 92, 43, 38, and 35%, respectively. Except for one case of Staphylococcus aureus septicemia, no major adverse events occurred. Conclusion Although limited by a considerable withdrawal rate, our observations strengthen our and other recent results further suggesting that IgE-selective IA is an effective treatment option for patients severely affected by AD with highly elevated IgE levels.